Customs Payments as Fiscal Instruments of the State - SLATVINSKA, M.; MIROSHNICHENKO, M. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The article examines the role and fiscal significance of customs payments in ensuring the state’s budgetary stability under martial law. It is substantiated that customs payments are not only a tool for generating budget revenues, but also an important regulator of foreign economic processes, protecting the national producer, and ensuring economic security. Approaches to the scientific understanding of customs payments as a fiscal instrument of the state are proposed based on the concept of fiscal imperatives, which determine the strategic guidelines of customs policy, administration mechanisms, and principles for ensuring transparency and efficiency of collection. Special attention is paid to the issue of the dynamics of customs revenues to the state budget in 2020–2024. Key problematic aspects of the functioning of the customs system in crisis conditions are analyzed. The main directions for increasing the efficiency of customs payments as a fiscal instrument of the state are identified. The fiscal imperatives of customs payments of the state under martial law are revealed: the imperative of ensuring fiscal stability; fiscal adaptability; transparency and digital openness; economic security; structural modernization. It is concluded that customs regulation and the customs system in particular need to be improved by digitalizing customs procedures, strengthening the analytical capacity of tax and customs authorities, as well as implementing European standards of transparency and accountability in the field of public finances.